2022
DOI: 10.1091/mbc.e21-05-0229
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of senescence-responsive stress fiber proteome reveals reorganization of stress fibers mediated by elongation factor eEF2 in HFF-1 cells

Abstract: Stress fibers (SFs), which are actomyosin structures, reorganize in response to various cues to maintain cellular homeostasis. Currently, the protein components of SFs are only partially identified, limiting our understanding of their responses. Here we isolate SFs from human fibroblasts HFF-1 to determine with proteomic analysis the whole protein components and how they change with replicative senescence (RS), a state where cells decline in ability to replicate after repeated divisions. We found that at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Doxycycline reduced the relative mRNA expression of MCP-1 (Control = 1.00 ± 0.08, ethanol = 2.90 ± 0.10, ethanol + doxycycline = 2.57 ± 0.11, n = 3, *** p < 0.001, * p < 0.05, Figure 6 C), E-selectin (Control = 0.95 ± 0.05, ethanol = 7.54 ± 0.36, ethanol + doxycycline = 6.00 ± 0.71, n = 3, *** p < 0.001, * p < 0.05, Figure 6 D), ICAM-1 (Control = 1.00 ± 0.13, ethanol = 8.52 ± 0.21, ethanol + doxycycline = 7.21 ± 0.38, n = 3, *** p < 0.001, ** p < 0.01, Figure 6 E) and VCAM-1 (Control = 1.00 ± 0.08, ethanol = 1.95 ± 0.19, ethanol + doxycycline = 1.41 ± 0.15, n = 3, *** p < 0.001, ** p < 0.01, * p < 0.05 Figure 6 F) in HUVECs treated with ethanol. The senescent cells are known to show impaired migration [ 24 , 25 ]; therefore, we investigated the effects of ethanol and ethanol combined with doxycycline on endothelial cell migration. Ethanol retarded the migration of HUVECs in wound assay, and doxycycline recovered the migration of HUVECs exposed to ethanol, percentage area covered by migrating endothelial cells at different time points after making a scratch (at 0 h: Control = 0.00 ± 0.01%, ethanol = 0.00 ± 0.00%, ethanol + doxycycline = 0.00 ± 0.00%, after 6 h: Control = 36.27 ± 7.03%, ethanol = 24.20 ± 5.36%, ethanol + doxycycline = 33.00 ± 25.87%, after 12 h: Control = 78.18 ± 7.57%, ethanol = 50.83 ± 9.41%, ethanol + doxycycline = 79.65 ± 4.35%, after 24 h: Control = 99.77 ± 0.23%, ethanol = 82.30 ± 13.40%, ethanol + doxycycline = 96.56 ± 5.64%, n = 3, ** p < 0.01, Figure 6 G,H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doxycycline reduced the relative mRNA expression of MCP-1 (Control = 1.00 ± 0.08, ethanol = 2.90 ± 0.10, ethanol + doxycycline = 2.57 ± 0.11, n = 3, *** p < 0.001, * p < 0.05, Figure 6 C), E-selectin (Control = 0.95 ± 0.05, ethanol = 7.54 ± 0.36, ethanol + doxycycline = 6.00 ± 0.71, n = 3, *** p < 0.001, * p < 0.05, Figure 6 D), ICAM-1 (Control = 1.00 ± 0.13, ethanol = 8.52 ± 0.21, ethanol + doxycycline = 7.21 ± 0.38, n = 3, *** p < 0.001, ** p < 0.01, Figure 6 E) and VCAM-1 (Control = 1.00 ± 0.08, ethanol = 1.95 ± 0.19, ethanol + doxycycline = 1.41 ± 0.15, n = 3, *** p < 0.001, ** p < 0.01, * p < 0.05 Figure 6 F) in HUVECs treated with ethanol. The senescent cells are known to show impaired migration [ 24 , 25 ]; therefore, we investigated the effects of ethanol and ethanol combined with doxycycline on endothelial cell migration. Ethanol retarded the migration of HUVECs in wound assay, and doxycycline recovered the migration of HUVECs exposed to ethanol, percentage area covered by migrating endothelial cells at different time points after making a scratch (at 0 h: Control = 0.00 ± 0.01%, ethanol = 0.00 ± 0.00%, ethanol + doxycycline = 0.00 ± 0.00%, after 6 h: Control = 36.27 ± 7.03%, ethanol = 24.20 ± 5.36%, ethanol + doxycycline = 33.00 ± 25.87%, after 12 h: Control = 78.18 ± 7.57%, ethanol = 50.83 ± 9.41%, ethanol + doxycycline = 79.65 ± 4.35%, after 24 h: Control = 99.77 ± 0.23%, ethanol = 82.30 ± 13.40%, ethanol + doxycycline = 96.56 ± 5.64%, n = 3, ** p < 0.01, Figure 6 G,H).…”
Section: Resultsmentioning
confidence: 99%
“…The migration of endothelial cells is an important process for angiogenesis and repair/healing of damaged tissue. Previous studies have reported that the senescent cells show retarded migration and are not efficient in the repair/healing of damaged tissue [ 24 , 25 ]. Ethanol treatment reduced the migration of HUVECs, and doxycycline significantly recovered the migration of ethanol-treated HUVECs ( Figure 6 G,H).…”
Section: Discussionmentioning
confidence: 99%
“…Our prediction is in agreement with experimental observations made on cells 41 . Exploring the involvement of other actin-regulating proteins 44 will be the subject of future challenging but exciting investigations, for which our approach would provide a basis. To this end, as we discussed just after the introduction of the overall entropy of Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Our prediction is in agreement with experimental observations made on cells (40). Exploring the involvement of other actin-regulating proteins (43) will be the subject of future challenging but exciting investigations, for which our approach would provide a basis. To this end, as we discussed just after the introduction of the overall entropy of Eq.…”
Section: Discussionmentioning
confidence: 99%